Modeling of water availability for food system transformation in Upper Offin Sub-basin and Mankran Micro-watershed of Ghana: scenarios analysis - Assefa, T. T.; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
Agriculture remains the primary livelihood in Ghana, marked by a growing emphasis on cocoa production nationwide. Existing research highlights the importance of supplementing rainfed cocoa production with irrigation. Simultaneously, mining has emerged as a key driver of the country's economic growth. However, there is an urgent need to assess the measurable impacts of cocoa production with supplemental irrigation and mining on water resources sustainability and quality. This study aims to investigate how the supplementary irrigation of coca and mining affects the water balance components and water quality, with a focus on sediment yield in Ghana. It builds upon a baseline study in the Upper Offin sub-basin and an upland watershed of the Mankran microwatershed using the Soil and Water Assessment Tool (SWAT) model. The analysis indicates that applying supplemental irrigation to 15% of the cocoa area from shallow groundwater would not significantly affect basin water yields. However, the impacts of supplemental irrigation on 5% of the cocoa area from shallow groundwater would significantly affect the groundwater flow in the Upper Offin sub-basin. Conversely, expanding supplemental irrigation to 38% of the cocoa area (with landscape slope less than 8%) and encompassing the entire cocoa area in the Mankran microwatershed significantly influences hydrology. In the Mankran micro-watershed, supplemental irrigation to all cocoa farms increased evapotranspiration, percolation, and sub-surface flow by up to 9%, 28%, and 21.5%, respectively. In contrast, catchment water yield has been decreased by 19% and groundwater flow ceased due to supplemental irrigation. On the other hand, mining in the Upper Offin watershed (covering 5% of the area) and the Mankran micro-watershed (covering 6% of the area) significantly impacted hydrology and sediment yield. Surface runoff, catchment water yield, and sediment yield increased, respectively by 28%, 7%, and 80% for the Upper Offin watershed. Similarly, the Mankran micro-watershed showed a significant increase in surface runoff, water yield, and sediment yield by 34%, 8%, and 147% due to mining. Percolation and groundwater flow significantly decreased in both the Upper Offin and Mankran micro-watershed. The findings indicate that expanding mining poses a challenge to cocoa production from shallow groundwater. Mining areas must identify suitable areas to minimiz adverse effects on irrigated cocoa production and implementation land reclamation on mined areas. Further research is required to refine the representation of mining activities in the SWAT model for more accurate results on the location and spatial coverage of mining impacts. The study underscores the necessity of context-specific management strategies, considering both agricultural and mining activities in water resource management plans for long-term environmental health and socio-economic viability.